Management of pediatric allergic reaction: Practice patterns of Canadian pediatric emergency physicians. Issue 6 (November 2020) - Prendergast, Caitlin; Plint, Amy C.; Tang, Ken; Crawford, Tyrus; Neto, Gina; Alqurashi, Waleed
ABSTRACT: Objectives: Anaphylaxis is a severe allergic reaction that can be life-threatening. The literature indicates that the incidence of anaphylaxis is increasing and that there are deficiencies in both recognition and management. We aimed to examine the magnitude of these gaps in Canadian pediatric emergency medicine (PEM). Methods: We conducted a self-administered survey of the Pediatric Emergency Research Canada (PERC) physician database. The survey tool was developed through a literature review to identify recurring themes of gaps in anaphylaxis diagnosis and management. The final tool contained four scenarios; three scenarios featured each of the National Institute of Allergy and Infectious Diseases (NIAID) anaphylaxis criteria, separately, and a fourth case of non-anaphylactic allergy. Multiple-choice questions associated with each scenario addressed diagnosis, management, and disposition. Additional questions focused on epinephrine prescribing, observation durations, and respondent demographics. Results: Of the 214 members invited to participate in the survey, 152 (71%) responded. Anaphylaxis was accurately recognized 93%, 82%, and 99% of the time for the NIAID criteria one through three, respectively. When anaphylaxis was recognized, epinephrine was prescribed for each case 96%, 95%, and 72% of the time, respectively. Of all respondents, 115 (76%) accurately diagnosed all three cases of anaphylaxis and 82 (54%) treated anaphylaxis with epinephrine each time it was indicated. Conclusion: Most respondents recognized cases of anaphylaxis; however, a substantial number demonstrated gaps in management that may adversely impact this vulnerable population. The recognition of anaphylaxis without urticaria or pulmonary findings and treatment of anaphylaxis with epinephrine, where indicated, were the main gaps identified.